Exploring the Promotion and Integration of Tujia Ethnic Group's "Meat Continuation" in Kindergarten Education - Yu, Qin (Journal of Theory and Practice of Contemporary Education, 2023)
To achieve true popularization, we have explored the promotion and integration of Tujia's "meat continuous sound" in kindergartens. I hope to take this opportunity to learn from experience and summarize methods, so that traditional folk culture can be more effectively promoted and integrated in kindergarten education.Enable the widespread promotion of folk culture among preschool children. So how to effectively promote and integrate folk culture in kindergarten education, we want to do some research on this. After searching for domestic and foreign literature, we found that there is very little research on this type of research, and there is very large research space. After multiple investigations, it was found that a kindergarten we collaborated with is promoting the Tujia dance "Meat Lianxiang". Therefore, we would like to conduct systematic research on the basis of the promotion of "Meat Lianxiang" in Lichuan Xinyi Kindergarten, so that traditional folk culture can be more effectively promoted and integrated in kindergarten education. The Ewenki people are devout followers of shamanism, and the "Er" is also full of corresponding religious colors. on the issue of the authenticity of life, the Evenki people believe that the soul exists apart from the body, so after death, the soul also has its own destination, either ascending to the sky, returning to the mountain, or entering the earth. "For the people of this tribe, death is just a change of life. Death is the beginning of another life, so they regard death as sacred and solemn. "